SHARING RESOURCES-SHARING COSTS/LE PARTAGE DES RESOURCES-LA PARTICIPATION AUX FRAIS: PROCEEDINGS OF THE SEVENTH CANADIAN CONFERENCE ON INFORMATION SCIENCE/COMPTES RENDUS DE LA SEPTIEME CONFERENCE CANADIENNE DES SCIENCES DE L'INFORMATION - Canadian Association for Information Science (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2022)
See PDF